THE VOICE OF DISCOURSE MULK RAJ ANAND’S SUBALTERN PERSPECTIVE IN UNTOUCHABLE - Kumar, Devashish (International Journal of Research -GRANTHAALAYAH, 2025)
Mulk Raj Anand’s novel Untouchable is a seminal work in Indian literature that provides a poignant and powerful narrative of the socio-economic and cultural discrimination faced by the Dalit community. This paper examines how Anand’s novel gives voice to the subaltern, focusing on themes of oppression, resistance, and the quest for dignity. Through a close analysis of the novel’s narrative structure, character development, and thematic concerns, this study highlights the ways in which Untouchable articulates the experiences of marginalized communities in colonial India. The paper also situates the novel within its historical and social context, emphasizing its role in challenging the rigid caste system and advocating for social reform and equality. By exploring these dimensions, this paper underscores the enduring relevance of Untouchable in the discourse on caste and social justice.